Determinant of Dental Caries in Pre-School Children at TK Permata Hati Bangkalan - Lidia Aditama Putri; Diani Octaviyanti Handajani (Universitas Muhammadiyah Malang, 2020)
Dental caries is one of the problems that often occurs in pre-school age children (3-6 years) as a result of unfavorable habits of children in maintaining dietary and brushing habits. The purpose of this study was to analyze the factors associated with the occurrence of dental caries in pre-school children. The type of research was observational analytic with cross sectional design. The samples were 81 children by using simple random sampling technique. The analysis of the data used univariate and bivariate using the Chi Square statistical test. The results showed that the factors associated with the occurrence of dental caries in pre-school children were the habit of eating cariogenic food (p = <0.001), the habit of drinking milk with a dot bottle (p = <0.001), the frequency of brushing (p = 0.004 ), and brushing time (<0.001). From 81 children which had been observed, 49 (60.5%) had dental caries, while 32 (39.5%) did not have caries. Therefore, serious efforts were needed to prevent dental caries in pre-school children by increasing the knowledge of mothers and pre-school children about proper and correct brushing procedures and encouraging mothers to have regular dental check-ups every 6 months, so that the problems related to oral health can be detected early.